ANALISA INVERSI ACOUSTIC IMPEDANCE (AI) UNTUK KARAKTERISASI RESERVOIR KARBONAT PADA LAPANGAN “X” FORMASI PARIGI CEKUNGAN JAWA BARAT UTARA - Luxy Rizal Fathoni; Udi Harmoko; Hernowo Danusaputro (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Acoustic Impedance (AI) inversion method has been applied to describe characterization of carbonate reservoir in the field “X” North West Java Basin. The aim of this research is to determine the distribution of hydrocarbon prospect area that based on AI value and porosity value parameters. The used of Acoustic Impedance (AI) inversion methods is model based methods. The of model-based method is consist of geologic model construction then we compare to the real seismic data. Then by assume linear relationship between AI log and porosity log, and we have a linear equation that used to obtain the porosity distribution from AI distribution. Inversion result shows porous limestone distribution which has porosity range value about 0,21 – 0,23 fraction and acoustic impedance range value about 6800 – 8000 gr/cc.m/s with the directional distribution northwest – southeast. Keywords: Acoustic Impedance, Limestone, Porosity, Model-based method